Estudo fitoquímico e da atividade antimicrobiana de Waltheria douradinha Saint Hilaire - Gressler, Vanessa (2006)
Native species of the flora from South Brazil are the aim of the research of the Núcleo de Pesquisa de Produtos Naturais of Federal University of Santa Maria, Brazil. One of the most studied families is the Sterculiaceae and, in that family, there is the Waltheria douradinha Saint Hilaire specie, study purpose of this master degree work. W. douradinha, popularly known as douradinha do campo , is used to treat lung infections, cystitis, chronic ulcer and to wash syphilitic wounds. Secondary metabolites isolated from the bark of the roots from this specie, among the amide (O)-metiltembamide, three known quinolone alkaloids, Antidesmone, Waltherione-A and Waltherione-B, two cyclopeptide alkaloids also known, Waltherine-A and Chamaedrine, and a new quinolone alkaloid VG8. The structures of these substances are determined, principally, by spectroscopics methods, like Nuclear Magnetic Resonance 1H and 13 C (COSY, HMQC e HMBC), mass spectrometry and by the comparison with melting point and literature data. The alkaloids Waltherione-A (WA) and Waltherione-B (WB) are crystallized and analyzed by X-Ray Diffraction to determine their relative stereochemistries. The extracts obtained from several parts of W. douradinha, the fractions obtained from the division of the crude extract of the root and the pure alkaloids, Waltherine-A, VG8, WA, WB and their derivatives were submitted to microbiologic assays (fungus and Gram-positive and Gram-negative bacteria) by bioautography method and by Minimum Inhibitory Concentration (MIC). The alkaloid VG8 was the most active upon the tested microorganisms, with a positive result of inhibition with 0.5 μg by bioautography assay and with 50 μg mL-1 by MIC assay.